SIMULTANEOUS EXTRACTION AND RAPID HPLC BASED QUANTIFICATION OF CROCIN AND SAFRANAL IN SAFFRON (CROCUS SATIVUS L.) - Alam, Pravej; Elkholy, Shereen F.; Hosokawa, Munetaka; Mahfouz, Sabry A.; Sharaf-eldin, Mahmoud A. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Saffron (Crocus sativus L.) is one of the most valuable crops with high medicinal values used in many diseases. The aim of the study was to establish the reliability and rapid HPLC method for analysis of crocin and safranal concentration present in stigmata of saffron in the market as well as field grown samples. Methods: Field grown and market stigmata of saffron were used for extraction of crocin and safranal. The linear dynamic ranges were established after validating the robustness of critical method parameters. The Agilent1260-Infinity Quaternary LC system was used for the preparation of calibration standards and quantification of crocin and safranal in C. sativus stigmata. Results: A good linearity was achieved in the range of 10-30 µg for each compound with the determination coefficient (R2). The calibration curves revealed linear regression (r. 0.997) for this rapid HPLC method and limit of quantifications (LOQs) were achieved in the range of 3.4 µg/ml for crocin and 10.2 µg/ml for safranal. The limit of detection (LODs) for all standards was ≤4.2 µg/ml. The range of crocin content (10.43-16.32 mg/g) and safranal (5.19-5.21 mg/g) was estimated in saffron samples. Conclusion: This method may serve the purpose of accurate quantification of crocin and safranal present in the stigmata of the plant in a quick time period. Keywords: Saffron, Crocin, Safranal, Extraction, Quantification, HPLC